Implementasi Digital Marketing Oleh UMKM Di Indonesia: A Scoping Review - Mochamad Sirodjudin; Sudarmiatin Sudarmiatin (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
Previous literature review studies have explored the current status of digital marketing implementation in Indonesia by the SME, a literature review that focuses explicitly on digital marketing implementation is scarce. The objective of this scoping review was to map the existing digital marketing knowledge to meet digital marketing practices. The scoping review followed the protocol outlined by Arksey and O'Malley (Arksey & O’Malley, 2005) that has five main stages: (1) identifying research questions; (2) identifying relevant studies; (3) study selection; (4) data charting, and (5) collating, summarizing and reporting the results. The reviewed studies were selected from two electronic databases: Scopus and Google Scholar within six years time span (2017-2023). The results of the scoping review indicated that the majority of the SME already knowing about digital marketing. However, as has been claimed by Aries Kurniawan and Asharudin (Kurniawan & Asharudin, 2018), SME have some obstacles that must be handle so they can survive and grow. Emphasis should be given to how to understanding digital marketing strategic and how to upgrade SME's knowledge about digital marketing. According to Katoyusyi Kano (Kano et al., 2022), digital marketing strategies from the consumer perspective should be given more attention in order to make digital marketing more effective in attracting attention and winning consumer trust.